2020
DOI: 10.1111/jon.12712
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cerebral Aneurysms: Comparing CTA, MRA, and Digital Subtraction Angiography Assessments

Abstract: BACKGROUND AND PURPOSE: Comprehensive imaging characterization of the morphology and luminal patency of cerebral aneurysms are cornerstones of their successful treatment and subsequent appropriate management. Giant cerebral aneurysms (GCAs), a distinct subgroup of aneurysms, are defined by large size (ࣙ 25 mm in greatest diameter), complex blood flow dynamics, and a high risk of rupture. The purpose of this study is to explore compare multiple imaging modalities in the assessment of GCAs. METHODS: This study r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Several studies have determined that CTA can replace DSA for aneurysm diagnosis, 28-30 especially for giant aneurysms. 31,32 We used CTA to diagnose giant aneurysms mimicking intraventricular tumors and used it as the main index of follow-up after aneurysm coil occlusion procedures, and the results of CTA are precise and stable. Aneurysms presenting as third ventricular masses have been studied in several limited cases between 1979 and 2020 because of the infrequency of this disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have determined that CTA can replace DSA for aneurysm diagnosis, 28-30 especially for giant aneurysms. 31,32 We used CTA to diagnose giant aneurysms mimicking intraventricular tumors and used it as the main index of follow-up after aneurysm coil occlusion procedures, and the results of CTA are precise and stable. Aneurysms presenting as third ventricular masses have been studied in several limited cases between 1979 and 2020 because of the infrequency of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…CT angiography is increasingly becoming a diagnostic tool for vessel pathology. 31 Aneurysms larger than 3 or 4 mm can be recognized with CTA. Teksam et al reported that CTA missed only seven out of 106 cases, and of these, only two were larger than 4 mm.…”
Section: Use Of Ct Angiographymentioning
confidence: 99%
“…11,29 CTA of clipped aneurysms has generally not been as accurate compared with conventional angiography, especially for small aneurysms, when multiple clips were used, on small parent vessels, or when the aneurysm was in the vicinity of bony structures. 12,[30][31][32] These same technical limitations may explain the trend toward lower agreement for clipped aneurysm subgroups assessed by CTA compared with coiled aneurysms assessed by MRA.…”
Section: Discussionmentioning
confidence: 99%
“…If the stenosis is serious and the blood flow speed is slow, thrombosis may be formed in the blood vessels. However, digital subtraction angiography (DSA) of the whole brain is unified as the “golden gold” for diagnosing the occurrence of AS in young IS sufferers [ 6 , 7 ]. The reason is that DSA can clearly show the distribution site and stenosis degree of AS and provide diagnostic criteria for subsequent therapy.…”
Section: Introductionmentioning
confidence: 99%